2020
DOI: 10.3389/fcell.2020.596452
|View full text |Cite
|
Sign up to set email alerts
|

High NESTIN Expression Marks the Endosteal Capillary Network in Human Bone Marrow

Abstract: Hematopoiesis is hosted, supported and regulated by a special bone marrow (BM) microenvironment known as “niche.” BM niches have been classified based on micro-anatomic distance from the bone surface into “endosteal” and “central” niches. Whilst different blood vessels have been found in both BM niches in mice, our knowledge of the human BM architecture is much more limited. Here, we have used a combination of markers including NESTIN, CD146, and αSMA labeling different blood vessels in benign human BM. Applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…13,28 The human BM vascular microarchitecture has been described in detail. 29 Like previous observations, we find nestin in endothelial cells of small arterioles and capillaries 30 and sub-endothelial perivascular cells. Nestin is upregulated in endothelial cells and in pericytes following BM transplant by IHC (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
“…13,28 The human BM vascular microarchitecture has been described in detail. 29 Like previous observations, we find nestin in endothelial cells of small arterioles and capillaries 30 and sub-endothelial perivascular cells. Nestin is upregulated in endothelial cells and in pericytes following BM transplant by IHC (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
“…CD271 stains for marrow stromal progenitor cells (37, 39, 40). CXCL12 and Nestin have also been shown to play a role in hematopoietic support within the human BM stromal compartment (41, 42). Using paraffin-embedded samples stored from the diagnostic workup of our patients, we stained consecutive sections and examined the presence of positive cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used MSC derived from different sources originated from mesoderm or extraembryonic tissue, such as BM, umbilical cord, adipose tissue, and placenta, in the therapeutic field as well as for hematologic disorders [ 10 ]. In this sense, the current studies have shown that nestin-positive mesenchymal stem cells (MSCs) are not only part of the HSC niche but are also required for HSC maintenance and hematopoiesis [ 52 , 53 ]. Based on this, we developed a novel and disruptive technology to isolate human immature dental pulp stem cells (hIDPSCs)—a special type of MSC that expresses high levels of nestin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%